Trabalhos embargados na BDTD-UFAM e o aproveitamento em geração de patentes dos cursos de pós-graduação da UFAM - Carvalho, Geyse Maria Almeida Costa de (2024)
The research aims to analyze the generation of patents based on works embargoed in the BDTD-UFAM by graduates of stricto sensu postgraduate courses at the Federal University of Amazonas (UFAM). To achieve this objective, bibliographic, documentary and field research methodologies were adopted, which allowed data collection and analysis of relevant information on the topic. The research exposes approaches related to the generation of patents and the embargo of academic production, in addition to understanding the legislation and standards related to the generation of patents and the embargo of academic production. The authors highlight the importance of seeking an appropriate balance between protecting the individual interests of researchers and promoting open access to scientific knowledge. The research results address the analysis carried out based on data obtained from UFAM information sources, linked to the Lattes Platform. These data reveal pertinent information as they indicate, for example, that 55 postgraduate programs made deposits in the Digital Library of Theses and Dissertations, metrically highlighting the quantity of deposits for each program. It carries out a metric analysis of embargoed works from 2010 to 2023. It is observed that, since 2010, there have been requests for restriction of access, totaling 354 embargoed theses and dissertations. Currently, there are 139 works that remain embargoed and 38 are for patent reasons, the rest are already available at BDTD. A survey of the authors' Lattes CVs and the database of the National Institute of Industrial Property (INPI) reveals 23 records of patent applications associated with these works. The predominance of patent applications in doctoral programs stands out, especially in the Postgraduate Program (PPG) in Biotechnology. The delay in granting patents is evident, suggesting complexity and slowness in the processes. Furthermore, 59 authors who had their work embargoed due to patents did not mention patent applications in their CVs. The research suggests changes to the deposit procedure and required documentation, including the formal participation of the Dean of Technological Innovation (PROTEC). It is also proposed to create a section on the institutional website dedicated to work that resulted in patents, reinforcing transparency and encouraging a culture of innovation in the institution. The disclosure of granted patents seeks to contribute to the advancement of the academic and scientific field, in line with the principles of democratization of knowledge and open access.